CROSS-CULTURAL FICTION IN FIRE EMBLEM FATES - Widjaya, Freddy Setiawan; Juanda; Supriadi, Asep (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
The purpose of this research is to analyze the cross-cultural fiction in Fire Emblem Fates. The data analysis based on qualitative method. Qualitative research as defined by Denzin and Lincoln (in Joubish, 2011, p. 2083) is a method which studies the things in the natural setting. The qualitative research is aimed to find the reasons and explanations, but not simply the description of the method of research and the sum of its results. For this analysis, the data uses the story from the game to analyze the cultural problem that is two different nations with different culture, as well as the effect on the main character who is trapped between the two nations at war. The result showed that cross-cultural affect the main character on the decision s/he will choose, whether s/he will choose to pick a side with one of the nations or make his/her own fate trying to make two nations at peace.